The investigation of 7S framework and organizational performance in the context of the hotel industry - Chareanporn, Tarittawan; Yoopetch, Chanin (Edelweiss Applied Science and Technology, 2025)
With the well-known 7S framework elements, this study explores the impact of the McKinsey 7S framework elements on organizational performance within the hotel industry in Thailand. The framework comprises seven key components: shared values, systems, staff, structure, style, strategy, and skills. The research specifically sought to identify which of these elements significantly influence hotel performance, providing insights into the critical factors within implementation strategies that drive organizational success. A quantitative research design was adopted, utilizing structural equation modeling (SEM) to analyze data collected from 380 hotel representatives across Thailand. The results demonstrated that six elements directly affect hotel performance, while style has an insignificant influence on performance. Findings reveal that six of the seven elements—shared values, systems, staff, structure, strategy, and skills—exert a significant direct influence on hotel performance. However, the element of style was found to have an insignificant effect. The study contributes both theoretically and practically by offering empirical evidence and managerial recommendations for enhancing organizational performance in the hotel sector. These insights can guide hotel managers and policymakers in refining strategic alignment using the 7S model.